PHILOSOPHICAL FOUNDATIONS OF THE HEALTH OF A SPIRITUAL AND MORAL PERSONALITY IN NEW UZBEKISTAN - Rajabov Otabek Atoevich (Web of Journals Publishing, 2025)
The article explores the philosophical foundations of the health of a spiritually and morally developed individual within the framework of the ideals and values of the New Uzbekistan. The author analyzes the interrelation between physical and spiritual health, emphasizing their significance in shaping a harmonious personality and a stable society. Special attention is given to cultural and ethical traditions, enlightenment principles, and the Islamic worldview that contribute to the development of a healthy lifestyle and moral maturity.
Keywords: Health, spirituality, morality, personality, philosophy of health, New Uzbekistan, harmony of body and soul, values, culture.